Developmental Toxicity of Dextromethorphan in Zebrafish Embryos/Larvae - Xu, Zheng (2010)
Dextromethorphan is widely used in over-the-counter cough and cold medications. Its efficacy and safety for infants and young children remains to be clarified. The present study was designed to use the zebrafish as a model to investigate the potential toxicity of dextromethorphan during the embryonic and larval development. Three sets of zebrafish embryos/larvae were exposed to dextromethorphan at 24 hours post fertilization (hpf), 48 hpf, and 72 hpf, respectively, during the embryonic/larval development. Compared with the 48 and 72 hpf exposure sets, the embryos/larvae in the 24 hpf exposure set showed much higher mortality rates which increased in a dose-dependent manner. Bradycardia and reduced blood flow were observed for the embryos/larvae treated with increasing concentrations of dextromethorphan. Morphological effects of dextromethorphan exposure, including yolk sac and cardiac edema, craniofacial malformation, lordosis, non-inflated swim bladder, and missing gill, were also more frequent and severe among zebrafish embryos/larvae exposed to dextromethorphan at 24 hpf. Whether the more frequent and severe developmental toxicity of dextromethorphan observed among the embryos/larvae in the 24 hpf exposure set, as compared with the 48 and 72 hpf exposure sets, is due to the developmental expression of the Phase I and Phase II enzymes involved in the metabolism of dextromethorphan remains to be clarified. A reverse transcription-polymerase chain reaction (RT-PCR) analysis, nevertheless, revealed developmental stage-dependent expression of mRNAs encoding SULT3 ST1 and SULT3 ST3, two enzymes previously shown to be capable of sulfating dextrorphan, an active metabolite of dextromethorphan.